Organization and management of Competitive Intelligence in Poland - Kij Magdalena (My University, 2006)
The aim of this thesis is to find out all the relevant information involved in Competitive Intelligence. In doing this, I will use the following method. The first chapter of my Bachelors thesis is called “The gist of Competitive Intelligence”. It starts by explaining what communication is, both verbal and non-verbal communication, and its linkage with the creation of civilizations. Generally, I want to show that communication everywhere in the world is a tool for sharing information and meanings and that interpersonal communication is the most common way of communicating. There is also great demand for precise and actual information, we are surrounded by information and can not exist without it. I will also explain what the causes of high demand for information are and what does it really mean for the market. Later on I would like to concentrate on the correlation between information and corporations. I would like to describe the internal and external factors that influence the success of a given company. Subsequently I will also mention globalization processes which result in the creation of international information, which is essential in conducting business abroad or with foreign people. After that I would like to introduce the reader to the field of competitive intelligence (shortened to CI). I would like to provide a few definitions and explain precisely what CI really is and what the advantages of this new discipline are. At this point I will describe what the sources are and the tools of CI and what are the required stages involved in the CI process. Consequently I would like to describe myths and facts of CI. Since CI is a relatively new concept, people tend to confuse it with different disciplines. I will mainly present differences between CI and Corporate Espionage and CI and Market Research. In the second chapter I will emphasize the psychological aspects of competitive intelligence. I will try to prove that there is a significant correlation between CI and psychology, since the CI agents’ work is mainly based on relations between human beings– which are the main subject of psychology. I would like to also explain what interpersonal relations, psychological persuasion and personality traits are and how we can apply them in terms of CI’s activities. In the third chapter I will describe the potential and attractiveness of the construction industry in Poland and I will present financial indicators of construction companies, demand and supply in this sector and many more. Afterwards I will mention the history of construction trade-fair’s in Poland and emphasize the most popular construction show in Europe-Budma. I will also describe the preparations of the WSB-NLU’s students for the trip to Poznan. I will attach a version of the survey which was conducted at the Budma 2006 tradefair and will describe what the aim of the trip was, what were the proceedings and recommendations from the fair.
Organizacja i zarządzanie wywiadownią gospodarczą w Polsce
Keywords: Competitive Intelligence (CI); psychology; business intelligence; communication; interpersonal communication; Poland